ANALISIS BREAK EVEN POINT (BEP) PADA PRODUK PINTU MEUBEL UD. NADYA GALUNGGUNG AMBON - Nadia Nadia; Grace Fredriksz; Frangky J. Louth (P3M Politeknik Negeri Ambon, 2022)
The purpose of this research is to calculate and analyze the break-even point on UD Furniture door products. Nadya Galunggung in 2019. The development of door product production at UD Furniture. Nadya Galunggung in 2019 it can be said that the amount of production is unstable, causing the number of production requests to fluctuate. So far, the magnitude of the benefits obtained is not known with certainty. Because until now the Furniture UD. Nadya Galunggung does not calculate the break-even point to plan their operating profit in the coming period.The data analysis technique used to analyze or calculate the break-even point on UD Furniture door products. Nadya Galunggung, the author uses a mathematical approach and a graphical approach and then proves the break-even point (TR=RC). From the analysis of the break-even point, it is expected that UD Furniture. Nadya Galunggung can use it as an input in developing company activities, especially in knowing the benefits.The conclusion of this paper is from the results of the calculation of break-even point analysis based on 2019 data, the production volume of UD Furniture doors. Nadya Galunggung obtained a break-even point in units of 241 units of doors and in rupiah of Rp. 438,508,000. Then the production volume of UD Furniture doors is obtained. Nadya Galunggung occurs when the production volume is 241 units of doors, if the selling price is considered fixed, namely Rp. 1,400,000 per door unit, then the revenue obtained at the break-even point is when the production volume value is Rp. 438,508,000. These figures can be a reference for UD Furniture. Nadya Galunggung to plan minimum sales to make a profit. Keyword: Break-even Point